An Evaluation of Laboratory Efficiency in Shanghai Emergency by Turn Around Times Level. Issue 4 (17th August 2014) - Lu, Yiming; Leong, Waiian; Wei, Bohua; Yu, Ping; Wang, Cuicui; Ying, Yilin; Wang, Tingsong; Tong, Jianjing; Zhu, Dingliang; Ye, Jing
<x xml:space="preserve">Abstract</x> Objective China launched a health care reform policy due to the aging population and rapid urbanization. However, emergency overcrowding is not improved. We assessed the laboratory efficiency of emergency department (ED) in Shanghai hospitals. Methods We recorded the turn around times for processing laboratory biomarkers to assess laboratory efficiency at 17 EDs in national/regional hospitals. We compared TAT between national and regional hospitals and between central and ED laboratories to analyze the relationship between the laboratory efficiency and the ED overcrowding. Results All the participating hospitals have an emergency laboratory. The median TAT for c‐TNT was 61 min (46–76 min) at regional EDs compared with 64 min (46–87 min) at national EDs; therefore, the TAT at regional EDs were more efficient (P < 0.05). The TAT were longer (65 min (53–85 min)) at ED labs than (60 min (42–83 min)) at central labs (P < 0.05), independent of the hospital tier and working period. We discovered that only 9% of investigated samples at Tier II EDs and 5% at Tier III EDs were assayed by point‐of‐care (POC) instruments. Conclusion Our TAT level is approaching the recommended international standard. However, the TAT evaluation from ED laboratories demonstrates that their existence does not decrease the waiting time for laboratory reports compared to central laboratory. Thus, they have not yet approached a level to share the burden of the ED overcrowding. Further arrangement should be assigned to separate the function of emergency laboratory and central laboratory. It is worth deploying the POC assay in the ED, which will save twice the TAT level. The idea of evaluating routine laboratory efficiency by TAT at ED is fast, convenient, although it does not represent the general level of laboratory efficiency.